Elements for debate about socio political investigation perspectives - Alpízar, Felipe (2012)
This paper discusses a sociopolitical research perspective by analizing the dimensions of the sociopolitical reality. The focus of this analisys is politics and power. Then, it tries to relate this dimensions with three forms of comprehension in social sciences and the debates about causality. It ends with a methodological proposal to study the social and political reality.